Impacto de las condiciones socioeconómicas familiares en las decisiones de fertilidad (número de hijos), utilizando un modelo de regresión poisson: período de estudio 2005-2006 - Bonilla Jaime, Gabriel (2009)
In this paper we attempt to emphasize the main socioeconomic determinants of the fertility decisions of Ecuadorian families, basing our study in the Becker and Lewis hypothesis (1973). The study presents a count data model, which describes fertility patterns observed in the household decision making process. In this regard, a poisson regression model of fertility decisions is applied.